The Cultural Message of Da’wah on The Jingkrak Sundang Dance in Central Java - Ali, Mukti; Wulandari, Isma Ayu; Muttaqin, Zaenal; Ma’mun, Sukron (KARSA Journal of Social and Islamic Culture, 2021)
This study aims to discuss the message of da’wah that is contained in the Jinkrak Sundang Dance by using a qualitative descriptive approach and using the technique of semiotic analysis. Semiotics seeks to find the signs with meaning and know the sign systems such as language, movement, music, and pictures. As for the objects of the material to be analyzed is the movement of dance performed by the Jingkrak Sundang Dance artist, located in Magelang. A semiotic analysis on the Jingkrak Sundang Dance is performed on each stage or round: Mlayu, Nebah Bumi, Laku Telu Dadung Ngawuk, Pati, Mendem, and Nawur. Jingkrak Sundang Dance depicts the anger of the animals whose habitat was marred by the man’s hand, who was not responsible. The da’wah messages were found in denotation and connotation that many charged theological and anthropological. Theologically, the da’wah message explains the belief in the power of God as creators and regulators of whole natural life. In contrast, the da’wah message emphasizes the anthropocentric, seen many messages that urge to keep, love, and affection among fellow creatures. This study shows the conveyed to society to preserve nature and survival of all living beings. In addition, human behavior with good acts, help, and practice at once be an example for human beings and caring for the sustainability of the nature of the other.